Impact of Environmental Factors on the Profit Efficiency of Rice Production: A Study in Vietnams Red River Delta (Global Journal of Human-Social Science, 2012)
Environmental factors affect agriculture production productivity and efficiency in which result in a change of profit efficiency. This paper seeks to estimate the impacts of environmental factors on the profitability of rice farmers in the Red River Delta of Vietnam. The dataset was compiled from personal interviews in 349 farmers. Both OLS and MLE translog profit functions were used in this study. Five production inputs and four environmental factors were included in those functions. The estimation of the stochastic profit frontier with a two-stage approach was used to measure profitability. The results showed that the profit efficiency was about 75% on average and various environmental factors influence profit efficiency significantly as well as beside farm specific characteristics. Plant disease, soil fertility, irrigation, and water pollution were the four environmental factors that caused profit loss in rice production. The results of the study indicated that farmers should reduce household size and the quantity of farm plots, apply a row seeding technique and improve environmental factors to obtain high profit efficiency. Special consideration should be given to irrigation infrastructure and water quality improvement.
Keywords: Tran-slog profit function; Rice Profitability; OLS and MLE estimations; Profit loss; Profit inefficiency